2020
DOI: 10.1111/jphd.12371
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and associated factors among adolescents aged 12 to 15 in Jiangxi Province, China

Abstract: Background The purpose of this survey was to examine the association of general characteristics, oral health knowledge, attitudes, behavior, and dental caries status among adolescents in Jiangxi Province and to provide a basis for future prevention of dental caries among middle school students. Methods A total of 8,160 adolescents aged 12 to 15 years were invited to participate in this survey by a stratified random cluster sampling method from 30 schools in five counties in Jiangxi Province. A self‐administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
1
9
2
Order By: Relevance
“…Similarly, the univariate analysis revealed that the tooth brushing was signi cantly more among NQC than QC. Although it is a foregone conclusion that good oral heath practices are protective against dental caries [30,31], the multivariate analysis didn't support this in our study. Taken together con rms, at least theoretically, that qat chewing negatively nulli es the positive effects of these factors.…”
Section: Discussioncontrasting
confidence: 88%
“…Similarly, the univariate analysis revealed that the tooth brushing was signi cantly more among NQC than QC. Although it is a foregone conclusion that good oral heath practices are protective against dental caries [30,31], the multivariate analysis didn't support this in our study. Taken together con rms, at least theoretically, that qat chewing negatively nulli es the positive effects of these factors.…”
Section: Discussioncontrasting
confidence: 88%
“…Female students had significantly higher prevalence of caries experience than males did, which was consistent with the survey findings of Zhejiang and Jiangxi provinces [ 14 , 17 ]. Some studies have pointed out that females are more prone to caries in comparison to males due to the following factors: teeth eruption occurs earlier in females, and comparatively slower saliva flow due to fluctuation of hormones during puberty [ 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, the univariate analysis revealed that the tooth brushing was significantly more among NQC than QC. Although it is a foregone conclusion that good oral heath practices are protective against dental caries [ 31 , 32 ], the multivariate analysis didn’t support this in our study. Taken together confirms, at least theoretically, that qat chewing negatively nullifies the positive effects of these factors.…”
Section: Discussioncontrasting
confidence: 78%